2012
DOI: 10.3797/scipharm.1205-16
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Taurine Against Methimazole-Induced Cytotoxicity in Isolated Rat Hepatocytes

Abstract: Methimazole is used as an antithyroid drug to control the symptoms of hyperthyroidism and maintain patients in a euthyroid state. Administration of this drug is associated with agranulocytosis and hepatotoxicity, which are the two most significant adverse effects. The present investigation was conducted to study the protective role of taurine against cytotoxicity induced by methimazole and its proposed reactive intermediary metabolite, N-methylthiourea, in an in vitro model of isolated rat hepatocytes.At diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…As demonstrated by cell proliferation assay, morphological examination and cell viability analysis, taurine could significantly promote chondrocyte growth. Previous research reported that taurine could effectively reduce methimazole-induced cytotoxicity in isolated rat hepatocytes (Heidari et al 2012), which corroborated this study by implying that taurine was non-cytotoxic. Some studies also reported that taurine played a role in promoting cell proliferation on neural stem/progenitor cells and human osteoblast cells (Hernandez-Benitez et al…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As demonstrated by cell proliferation assay, morphological examination and cell viability analysis, taurine could significantly promote chondrocyte growth. Previous research reported that taurine could effectively reduce methimazole-induced cytotoxicity in isolated rat hepatocytes (Heidari et al 2012), which corroborated this study by implying that taurine was non-cytotoxic. Some studies also reported that taurine played a role in promoting cell proliferation on neural stem/progenitor cells and human osteoblast cells (Hernandez-Benitez et al…”
Section: Discussionsupporting
confidence: 79%
“…It has extensive clinical application not only in the central nervous system and the reproductive system (Lobo et al 2000;Menzie et al 2014), but also in the cardiovascular system (Guidotti and Giotti 1970;Satoh and Kang 2009) and the endocrine system (Silaeva and Dokshina 1980). Its cytoprotective role has been reported in various cell types, including hepatocytes, vascular smooth muscle cells, and PC12 rat pheochromocytoma cells (Kearns and Dawson 2000;Li et al 2004;Heidari et al 2012). It could also stimulate cell proliferation in neural stem/progenitor cells, neural progenitor cells and osteoblast cells (Jeon et al 2007;Hernandez-Benitez et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The most toxic was simvastatin, but CoQ 10 effectively reduced cell death induced by all the statins. Statins significantly depleted cellular glutathione reservoirs (Figure 1) and increased the levels of oxidised glutathione (Figure 2), which is an indicator of oxidative stress (22). Thirty-minute pretreatment of hepatocytes with CoQ 10 significantly lowered GSSG and increased GSH levels (Figure 1 …”
Section: Resultsmentioning
confidence: 99%
“…Absorbance was recorded by a Pharmacia Biotech Ultrospec ® 2000 spectrophotometer (Cambridge, UK) at 532 nm after treating 1.0 mL aliquots of hepatocyte suspension (10 6 cells mL -1 ) with trichloroacetic acid (70 %, w/v) and boiling the supernatant with thiobarbituric acid (0.8 %, w/v) for 20 min (22).…”
Section: Lpo Assaymentioning
confidence: 99%
“…Animals had free access to food and water. Collagenase perfusion method was used to isolate rat hepatocytes (14). This technique is based on liver perfusion with collagenase after the removal of calcium ion (Ca…”
Section: Hepatocyte Preparationmentioning
confidence: 99%